Perancangan Penataan Gudang Finished Goods pada PT. Trias Sentosa, Tbk Menggunakan Metode ABC Analysis - Matthew Ansell Tandoko; Nova Sepadyati (Jurnal Titra, 2020)
PT. Trias Sentosa, Tbk is one of the biggest major manufacturer of flexible packaging film manufacturer producing BOPP (Biaxially Oriented Polypropylene) & BOPET (Biaxially Oriented Polyester) Film Products. PT. Trias Sentosa, Tbk has a worldwide sales and distribution network, from Indonesia to Asian countries and the Middle East. Warehouse layout management should be of a concern for companies. PT. Trias Sentosa, Tbk in this case, hasn’t applied a measured method to managing their finished goods warehouse layout. A study is conducted to improve the warehouse layout using ABC analysis method. ABC analysis is used to compare the displacement flow of goods in its current layout and the improved state. ABC analysis method are done by analyzing the delivery frequency of finished goods and the finished goods warehouse’s dimensions. The expected result should be that the best layout has the least total displacement value, and that layout is going to selected and applied.